Measuring the Performance of Posyandu Cadres using the Topsis Method - Muhamad Muslihudin; Dian Kusmawati; Riki Riki (Institut Bakti Nusantara, 2021)
Dijen Binakesmas posyandu Depkes RI (2009) found out that the performance of posyandu cadres decreased, it was known because the coverage of toddlers who came to posyandu fell from 60 % to 43% resulting in many children who do not receive posyandu services and can result in malnutrition. POSYANDU (Posyandu Service Post) is one form of community-based effort. The success of a posyandu is influenced by the active activities of a cadre. The TOPSIS method is one of the multicentric methods of decision-making. To simplify the assessment of cadre performance using the Technique for Order Preference method by Similarly to Ideal Solution. The purpose of this study was to obtain a model of decision-making on the posyandu cadre performance appraisal with the topsis method. The criteria that are determined include age, education, occupation, years of service, achievements. The results of this study obtained that the alternative V6 with a value of 0.8242 was the performance of the best posyandu cadre.